Neuroprotective role of carvacrol in ischemic brain injury: a systematic review of preclinical evidence and proposed TRPM7 involvement - Khojah, Abdulrahman M.; Al Dera, Hussain (Frontiers in Pharmacology, 2025)
IntroductionCarvacrol, a phenolic monoterpene and putative TRPM7 inhibitor, has demonstrated neuroprotective activity in cerebral ischemia models. This systematic review synthesizes preclinical evidence on carvacrol across focal and global ischemia, separating outcomes by disease model and summarizing mechanisms of action and translational barriers.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, PubMed, ScienceDirect, and Google Scholar were searched from inception to 06-20-2025. Inclusion criteria (PICOS) targeted rodent models of focal (MCAO or hypoxia–ischemia) or global ischemia (BCCAO), with carvacrol administered systemically or centrally and reporting infarct size, behavior, oxidative stress, apoptosis, or pathway markers. Dual, independent screening, extraction, and SYRCLE risk-of-bias appraisal were performed. A prospectively registered protocol (KAIMRC NRR25/050/9) guided this review.ResultsSeven studies met criteria. In focal ischemia (3 studies), individual experiments reported reduced infarct volume (up to 44%) and improved neurological scores when carvacrol was given before or shortly after injury. In global ischemia (4 studies), carvacrol improved memory/behavioral outcomes and neuronal survival in hippocampal CA1, with mixed effects on infarct surrogates. Across models, studies showed reduced oxidative damage (MDA, 4-HNE), increased antioxidant enzymes (SOD, CAT, GPx), lower apoptosis (cleaved caspase-3), and variable changes in TRPM7 expression. No study directly linked carvacrol’s outcome benefits to contemporaneous measurement of TRPM7 channel activity in vivo.ConclusionCarvacrol demonstrates promising neuroprotective signals in both focal and global ischemia models, with convergent antioxidant and anti-apoptotic effects and suggestive TRPM7 involvement. However, evidence certainty is limited by small study numbers, heterogeneity, and methodological risks. Translation will require optimization of delivery, improved study design aligned with STAIR, and mechanistic validation using selective TRPM7 modulators.Systematic Review Registrationidentifier NRR25/050/9.